The impact of job stress on job satisfaction and turnover intentions among bank employees during the COVID-19 pandemic - Lin, Mei-Hui; Yen, Ya-Hui; Chuang, Tsai-Fu; Yang, Ping-Sen; Chuang, Ming-Da (Frontiers in Psychology, 2024)
The main objective of this study is to explore the relationships among job stress, job satisfaction, and turnover intentions among bank employees during the COVID-19 pandemic, with an emphasis on variations across different demographic characteristics. Employing a cross-sectional design, data were gathered from 501 bank employees via the Job Stress Questionnaire (JSQ), the Simplified Minnesota Satisfaction Questionnaire (MSQ), and the Intention to Leave Scale (ILS). The research hypotheses were tested through descriptive statistics, t tests, ANOVA, Pearson correlation, and multiple regression analyses. The results indicate that job stress is significantly negatively correlated with job satisfaction and positively correlated with turnover intention. Interpersonal relationship stress was identified as the strongest predictor of turnover intention, whereas job autonomy stress significantly influenced job satisfaction. Demographic factors-particularly age, income, and education level-moderated these relationships, with younger, higher-income, and more educated employees reporting lower stress and higher satisfaction. Compared with those without dependents, those with dependents reported higher stress levels, lower job satisfaction, and greater turnover intentions. This study highlights the importance of managing workplace stress and enhancing job satisfaction to reduce turnover intention, particularly in the context of the COVID-19 pandemic. Interventions aimed at improving interpersonal relationships and providing targeted support for older and lower-income employees are recommended to mitigate stress and improve retention rates.